Conflicts and violence in prison, 1998-2000 - Edgar, Kimmet (UK Data Service, 2003)
By their nature, prisons engender potentially violent conflicts; this research project explored the circumstances which led to violence in prisons; the consequences of violent confrontations for prisoners and staff; and the ways in which conflicts with the potential to lead to violence were resolved without recourse to physical force. This project sought to understand why a particular situation became violent and to what extent the violence was considered to have settled the matter. The study took place in four different types of establishment: a high security prison, a local prison, a women's prison, and a young offender institution. The main aims and objectives were: 1. To analyse inter-personal violence in penal institutions; to explore the circumstances in which conflicts escalate into physical injury or threats to safety. 2. To identify methods of communication, conciliation, or mediation used by staff and inmates to reduce the likelihood of a violent outcome; to outline the interests of perpetrators and victims, how they interpret their actions and the norms that guide their decision-making. 3. To assess the response of the institution and to assess whether the official response played a role in resolving such conflicts. 4. To clarify the conditions under which the use of force by inmates or staff is considered acceptable; to examine the circumstances in which staff decide that 'control and restraint' techniques are required. 5. To compare the forms of violence in different types of population, distinguished by the age, gender and race of prisoners and staff.